PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA MUARA MAHAT BARU KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2015-2017 - Dony Apriyanto; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to increase community participation in village development based on law number 6 of 2014 concerning villages, government regulation of the republic of Indonesia Number 43 of 2014 concerning Villages and government regulation Number 60 of 2014 concerning Village Funds. The success of this development does not escape the support and community participation, in this case it can be said that the community has the most important position in the development process. Community participation in Muara Mahat Baru Village is still at a minimum in musrenbang, and musrenbang cannot accommodate interests and there is still minimal development of basic needs such as educational support facilities. The type used in this research is descriptive research with a qualitative research approach. The type of research data is primary data. and secondary data. The data collection techniques in this study were documentation and interviews. The data analysis technique used was descriptive qualitative data analysis.The results showed that community participation was not optimal in relation to the development being carried out. This can be seen from the minimal involvement of the community in development planning where the presence of the community to participate in compiling and discussing the RPJMDes is still lacking, because the village government is still lacking in socialization. Development carried out in 2015-2017 only focused on Hamlet I and Dusun III, while other hamlets were still not actively participating. The factors that hinder community participation are the factor of village apparatus resources, the limited source of funds, while the community's unlimited needs.  Keywords: Community Participation, Village Development